Chemiresistors Based on Li-Doped CuO–TiO2 Films - Alfio Torrisi; Jiří Vacík; Giovanni Ceccio; Antonino Cannavò; Vasily Lavrentiev; Pavel Horák; Roman Yatskiv; Jan Vaniš; Jan Grym; Ladislav Fišer; Martin Hruška; Přemysl Fitl; et al. (Chemosensors, 2021)
Chemiresistors based on thin films of the Li-doped CuO–TiO2 heterojunctions were synthesized by a 2-step method: (i) repeated ion beam sputtering of the building elements (on the Si substrates and multisensor platforms); and (ii) thermal annealing in flowing air. The structure and composition of the films were analyzed by several methods: Rutherford Backscattering (RBS), Neutron Depth Profiling (NDP), Secondary Ion Mass Spectrometry (SIMS), and Atomic Force Microscopy (AFM), and their sensitivity to gaseous analytes was evaluated using a specific lab-made device operating in a continuous gas flow mode. The obtained results showed that the Li doping significantly increased the sensitivity of the sensors to oxidizing gases, such as NO2, O3, and Cl2, but not to reducing H2. The sensing response of the CuO–TiO2–Li chemiresistors improved with increasing Li content. For the best sensors with about 15% Li atoms, the detection limits were as follows: NO2 → 0.5 ppm, O3 → 10 ppb, and Cl2 → 0.1 ppm. The Li-doped sensors showed excellent sensing performance at a lower operating temperature (200 °C); however, even though their response time was only a few minutes, their recovery was slow (up to a few hours) and incomplete.